On the actual identity of the genus Castianeira Keyserling, 1879 (Araneae: Corinnidae: Castianeirinae): the type species and its relatives - Silva-Junior, Cláudio J.; Bonaldo, Alexandre B. (Zootaxa, 2026)
The identity of the type species of Castianeira Keyserling, 1879 is clarified, enabling a diagnosis of Castianeira sensu stricto, which comprises four species from northern South America and Panama. The type species, C. rubicunda Keyserling, 1879, is recorded from Venezuela, Colombia, and Panama, with the specimens from Barro Colorado Island (Panama) having previously been misidentified as C. memnonia (C. L. Koch, 1841). Based on photographs of the holotype of the later species, it is transferred to Mazax O. Pickard-Cambridge, 1898 and recognized as the senior synonym of M. mokana Silva-Junior, Martínez, Villarreal & Bonaldo, 2024 syn. nov.. Since M. memnonia comb. nov. is the type species of Thargalia Karsch, 1880, Thargalia is removed from the synonymy of Castianeira and treated as a synonym of Mazax, as a nomen oblitum, while Mazax is declared a nomen protectum under the provisions of the International Code of Zoological Nomenclature. Three new species are described: Castianeira leda sp. nov. (♂) and C. pollux sp. nov. (♂♀), both from Colombia, Peru, and Brazil, and C. castor sp. nov. (♂♀) from Venezuela and Brazil.